Effect of resveratrol administration on muscle glycogen levels in rats subjected to acute swimming exercise - Bicer, Mursel; Baltaci, Saltuk Bugra; Mogulkoc, Rasim; Baltaci, Abdulkerim Kasim; Avunduk, Mustafa Cihat (Cellular and Molecular Biology, 2019)
The present study aims to examine how resveratrol administration affects muscle glycogen levels in rats subjected to an acute swimming exercise bout. The study was conducted on adult male rats of Wistar-Albino. The 28 rats used in the study were equally divided among four groups: Group 1, Control Group: The group fed on a standard diet and not subjected to any procedure. Group 2, Control Swimming Group: The group fed on a standard diet and subjected to an acute swimming exercise bout for 30 minutes at the end of the study. Group 3, Resveratrol Group: The group fed on a standard diet and given (10 mg/kg) resveratrol in drinking water for four weeks. Group 4, Resveratrol + Swimming Group: The group fed on a standard diet, given (10 mg/kg) resveratrol in drinking water for four weeks and subjected to a 30-minute acute swimming exercise at the end of the study. At the end of the four weeks, the animals were decapitated, muscle glycogen levels using immunohistochemical method. The highest muscle glycogen levels were obtained in the resveratrol-administered Group 3 and the lowest levels in group 2 (swimming group) (p<0.05). The results of the study demonstrate that resveratrol support had a protective and/or regulatory effect on mucle glycogen in both exercised and not-exercised rats.